Chemical characterization of a glycosylated cyanidin obtained from Kalanchoe laetivirens extracts and evaluation of its antimicrobial potential (Research, Society and Development, 2021)
The species Kalanchoe laetivirens is a succulent from tropical areas such as Africa and Asia. Due to the favorable climate, this plant was introduced in Brazil where it is used as a medicinal alternative for the treatment of diseases such as infections, inflammations, diarrhea and wound healing. The compounds present in this organism belong, for the most part, to the class of flavonoids with antioxidant, gastroprotective, antiulcer, kidney stones, bacterial and viral infections. Thus, the objective of this work was to investigate the chemical compounds present in crude extracts and their fractions, as well as to verify their antimicrobial potential. For this, the plant sample was subjected to extraction with 70% ethanol and then fractionated with hexane, chloroform and ethyl acetate. Such extracts were analyzed in high performance liquid chromatography coupled to a mass spectrometer to verify the ions present in the samples. 3,7-di-O-rhamnosyl-cyanidin was found to be a glycosylated cyanidin. Its antimicrobial activity was determined to be negative against the tested pathogens.